Demand of ICT-based chemistry learning media in the disruptive era - Ratna Kumala Dewi; Sri Wardani; Nanik Wijayati; Woro Sumarni (International Journal of Evaluation and Research in Education (IJERE), 2019)
The challenges of education in the era of the industrial revolution include disruption 4.0, 21st-century skills, globalization, and global competition. Chemistry is a subject that needs to be developed in order to improve the educational system in the era of disruption. The purpose of this research is to identify and analyze the needs of the media-based chemistry study ICT at grade X redox materials in State Senior Highschool 8 Semarang during the disruption. The method used in this research is a descriptive qualitative method which consists of the study of literature and the study of the field. Method of data collection is done through observation, question form, documentation, interview teachers, as well as interview students. This research instrument consisting of a sheet of observation, question form, and sheet interview. The results showed that chemical-based learning media limited ICT in State Senior Highschool 8 Semarang redox materials especially in class X. That is because of the teacher's difficulty in innovating to develop learning media chemistry-based ICT and lack of student understanding and literacy in the study of chemical materials. Teachers play an important role in order to educate the students towards the era of disruption. In this era of chemical subjects not only taught students with literacy (reading, writing, math) but the need for a new form of literacy the literacy data, technology, and human resources in order to overcome learning difficulties and improving students learning outcomes for better value.